2014
DOI: 10.1097/rli.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

The Protein and Contrast Agent–Specific Influence of Pathological Plasma-Protein Concentration Levels on Contrast-Enhanced Magnetic Resonance Imaging

Abstract: OBJECTIVE: The objective of this study was to measure the protein-specific response of r1 and r2 relaxivities of commercially available gadolinium-based magnetic resonance imaging contrast agents to variation of plasma-protein concentrations. MATERIALS AND METHODS: In this in vitro study, contrast agent (gadofosveset trisodium, gadoxetate disodium, gadobutrol, and gadoterate meglumine) dilution series (0-2.5 mmol Gd/L) were prepared with plasma-protein (human serum albumin [HSA] and immunoglobulin G [IgG]) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…This may be due to the fact that the acidic environment can weaken the chelation of EGCG and Mn, thereby substantially accelerating the release of Mn 2þ . Furthermore, the difference in relaxivity may also be associated with the different experimental conditions used, as there are many factors that can influence relaxivity, including solvent type, incubation time, and even temperature (Hao et al, 2012;Goetschi et al, 2014). L-EGCG-Mn NPs also showed pH sensitivity in terms of shortening the T 2 relaxation time, which is similar to previous studies (Chen et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…This may be due to the fact that the acidic environment can weaken the chelation of EGCG and Mn, thereby substantially accelerating the release of Mn 2þ . Furthermore, the difference in relaxivity may also be associated with the different experimental conditions used, as there are many factors that can influence relaxivity, including solvent type, incubation time, and even temperature (Hao et al, 2012;Goetschi et al, 2014). L-EGCG-Mn NPs also showed pH sensitivity in terms of shortening the T 2 relaxation time, which is similar to previous studies (Chen et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…T1 relaxivity, known as r 1 , is influenced by many variables including magnetic field strength, temperature, environmental conditions, and protein concentration. 1,[3][4][5] Previous in vitro studies have examined the relative relaxivities of the Gd chelates. However, these have been incomplete (not including all relevant field strengths or deriving calculations from a wide range of concentrations), inapplicable to human imaging (not performed in human whole blood at physiologic temperatures), or failing to account for nonlinear 1/T1 vs [Gd] when proteins are present for the proteinbinding agents.…”
mentioning
confidence: 99%
“…Previously, the relaxivities of gadoxetate, gadobenate, and gadoterate were compared in different media: Rohrer et al [ 18 ] found that the relaxivity of gadobenate was similar to gadoxetate, and that these two contrast agents exhibited higher relaxivities than gadoterate in water, plasma, and blood with a T1-weighted TSE sequence at 1.5-T (blood) and 3-T (water, plasma) MRI. Moreover, Goetschi et al [ 19 ] found higher relaxivity of gadoxetate compared with gadoterate in saline. To compare our results to these studies, we focused on a specific contrast agent concentration of 0.25 mM which is most comparable to other literature reports.…”
Section: Discussionmentioning
confidence: 99%